EKSPANSI KOMODITI AGRIBISNIS UNGGULAN DAN TINGKAT KEMISKINAN DI KABUPATEN PIDIE - Safrika, Safrika; Hamdani, Hamdani; Julia, Julia (Universitas Galuh, 2023)
This study aims to determine how the influence of leading agribusiness development in efforts to reduce poverty in the Pidie district. This research was conducted in March 2023. There were 74 samples from a population of 3,717 leading commodity farmers in Pidie Regency. Collecting data using observation, questionnaires, interviews, and documentation. The method used is qualitative and quantitative analysis. The simple linear regression method was used to see the effect of X and Y variables. The results showed that the development of leading agribusiness commodities had an effect on poverty alleviation in the Pidie district. This is due to the fact that developing leading agribusiness is very helpful for the family economy, because the land cultivated is own land, so income is higher, moreover the land cultivated is wider than small land. Leading agribusiness commodities are still in great demand by the agricultural market and this is a great opportunity for the government to synergize with farmers in tackling the poverty rate in Pidie District.